Family planning and preimplantation testing: family experiences in congenital adrenal hyperplasia - Sandy, Jessica L.; Betts, Grant; Harper, Jessica L.; Nevin, Suzanne M.; Deans, Rebecca; Neville, Kristen A. (Frontiers in Endocrinology, 2025)
IntroductionPre-implantation testing (PGT) is often suggested by healthcare professionals (HCP) to parents of children with congenital adrenal hyperplasia (CAH) considering subsequent children. Despite this, some families choose to conceive naturally without genetic testing and intervention. The aims of this study were to explore fertility choices of couples with a child with CAH and the decision making process and perceptions behind these choices, and to explore the families’ lived experiences with CAH and the couples’ subsequent fertility journey. A better healthcare professional understanding of these experiences may subsequently help guide clinicians to better manage and support families of children with CAH and other autosomal recessive conditions.MethodsAll parents of current children of a tertiary service in 2020 with 21-hydroxylase deficient CAH who made an active decision regarding family planning after diagnosis of their index child were invited to participate in a semi-structured interview. Thematic analysis was performed using an inductive, semantic approach.ResultsThirty families (34 children) were identified. Fourteen considered subsequent children and had directed genetic counselling. Eight decided to have additional children of whom seven agreed to participate. Thematic analysis identified six key domains. Psychological impact surrounding the CAH diagnosis was long-lasting, causing symptoms of trauma including depression and anxiety, and influencing a couple’s choice to pursue PGT to avoid having another affected child. The perception of the index child having a mild phenotype, and fear of a more severe phenotype, often supported this decision. Conversely, lived experience of CAH and low day-to-day impact, along with a negative experience of PGT, with a greater than anticipated financial, physical, and emotional toll, led some families to subsequently consider natural conception. The role of the healthcare professional (HCP) was important in the CAH and family planning journeys. A perceived poor understanding of CAH, overstating its potential seriousness, contributed to distress. Parents reported feeling pressured to undergo PGT. Peer-support had a universally positive impact on family experience.Discussion/conclusionsThis study highlights the complex and dynamic nature of fertility decision-making, and the importance of HCP empathy and open-mindedness. Education of HCP and encouraging peer support may improve the CAH and fertility journey for families.